ANALISIS HUKUM SECARA ANALOGI PENERAPAN ASAS PEMISAHAN HORIZONTAL PADA PRAKTEK JUAL BELI TANAH TIDAK BESERTA DENGAN POHON KELAPA DI ATASNYA DI KEC. PATILANGGIO KAB. POHUWATO - Nasrullah, Nasrullah (Jurnal Hukum Volkgeist, 2018)
The principle of horizontal separation in the LoA is a principle that separates the ownership of the land by the right to the property on the ground or attached to the land, where the existence of the object attached to the land there is a time limit provision either by agreement or on the basis of the provisions of the legislation.Based on the analogy of law in the above analogy, it can be concluded that the practice of buying and selling land is not accompanied by coconut trees on it also apply the principle of horizontal separation due to the separation or difference of legal subject holder of property rights to the land with legal subject holder of property rights on coconut trees . But if you look at the various legal bases in the BAL which regulate the principles of horizontal separation such as Right of Use, Right of Use, Right to Use, Lease of Land for Building Establishment, Right of Ride, and Lease of Land for Agriculture all have clear clear time limits on the basis of agreement and also on the basis of the provisions of legislation. And for the duration of the term is not over so long also the holder of property rights on the land should not use his right either to build the building, manage or make it as collateral (collateral) debts and so on. While in the sale and purchase of separate land with coconut trees on it is not so, because there is no provision of clear time limit of the existence of coconut trees on the land rights of others and holders of land rights are still entitled to grow crops on their property rights. So the basic difference is what distinguishes the application of the principle of horizontal separation in BAL with the principle of separation of horisoltan on the practice of buying and selling land is not accompanied by coconut trees on it.